2012
DOI: 10.1002/elps.201200307
|View full text |Cite
|
Sign up to set email alerts
|

Distinct cerebrospinal fluid amyloid‐beta peptide signatures in cognitive decline associated with Alzheimer's disease and schizophrenia

Abstract: Mild alterations in cognitive function are present in normal aging and severe cognitive alterations are a hallmark of Alzheimer's disease (AD). Cognitive deficits are prevalent in patients with schizophrenia (SCZ) and worsen with old age. We recently reported that elderly SCZ patients show reduced levels of amyloid-beta (Aβ)1-42 in cerebrospinal fluid (CSF). To further clarify the role of Aβ in cognitive decline, we analyzed the whole panel of CSF Aβ isoforms in elderly SCZ patients as well as in sporadic AD u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
22
0
4

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 27 publications
3
22
0
4
Order By: Relevance
“…higher cortical Aβ) in SCZ relative to ECs. Albertini et al (2012) saw an overall reduction in almost all types of CSF Aβ species and significantly reduced CSF Aβ1-42 in the SCZ group in comparison to the EC group [51]. …”
Section: Resultsmentioning
confidence: 99%
“…higher cortical Aβ) in SCZ relative to ECs. Albertini et al (2012) saw an overall reduction in almost all types of CSF Aβ species and significantly reduced CSF Aβ1-42 in the SCZ group in comparison to the EC group [51]. …”
Section: Resultsmentioning
confidence: 99%
“…In addition to previously identified AD-associated proteins, such as APP, transferrin, α1β-glycoprotein, complement components, afamin precursor, spondin 1, plasminogen, hemopexin, and neuronal pentraxin receptor, the study also identified a number of unique proteins including calsyntenin 3, AMPA (α-amino-3-hydroxy-5-methyl-4-isoxazolepropionic acid) 4 glutamate receptor, CD99 antigen, di-N-acetyl-chitobiase, and secreted phosphoprotein 1 (Ringman et al, 2012). SELDI-TOF-MS was recently applied to characterize CSF Aβ peptide isoforms in sporadic PD (Albertini et al, 2012). This study used immunoproteomic approach and identified Aβ1-42 as a potential biomarker for AD.…”
Section: Alzheimer's Diseasementioning
confidence: 99%
“…The majority of these proteomic studies were performed using 2-DE followed by MALDI-TOF-MS [48,50,53] or by using SELDI-TOF-MS [40,49,51,54]. Only one study [52] uses label-free MS E , an approach where the fragmentation spectra of virtually all the peptides resulting from protein digestion is acquired [60].…”
Section: Biomarker Discovery In Csfmentioning
confidence: 99%